Defects formation in spinel crystals under electron and gamma beam irradiation - Gokov, S.P.; Gritsyna, V.T.; Kochetov, S.S.; Kasilov, V.I.; Kazarinov, Yu.G. (Вопросы атомной науки и техники, 2009)
There were investigated the optical absorption centers formation in magnesium aluminate spinel crystals at the action of high energy gamma or electron beams. It was revealed that at gamma irradiation the most probably the hole centers are formed to compare with that in electron irradiation. At electron beam irradiation the temperature of sample was raised which leads to thermal annealing of unstable radiation-induced centers. Проведено дослідження утворення оптичних центрів поглинання в монокристалах магнійалюмінієвої шпінелі під дією високоенергетичних гама- або електронних пучків. Установлено, що гама-опромінення призводить переважно до утворення діркових центрів. При електронному опроміненні настає підвищення температури зразка, що призводить до термічного відпалу нестабільних радіаційно-наведених центрів. Проведены исследования образования оптических центров поглощения в монокристаллах магний-алюминиевой шпинели при воздействии высокоэнергетических гамма- или электронных пучков. Установлено, что гамма-облучение приводит преимущественно к образованию дырочных центров. При электронном облучении происходит повышение температуры образца, что приводит к термическому отжигу нестабильных радиационно-наведенных центров.